A Randomized Controlled Blind Clinical Trial: The Effect of Probiotics-Containing Milk Supplementation on Morbidity and Mortality due to Acute Diarrhea in Infants and Children in Sana’a, Yemen - Elnemr, Muna A. M. (University of Science and Technology, Sana'a, 2010)
Objective: To study the impact of probiotic-containing milk administration on the morbidity and mortality attributed to diarrhea among children less than 5 years old. Methods: The study design was a randomized blinded controlled clinical trial, held at Elsabeen Hospital for Maternity and Childhood in Sana'a city, Yemen. The study was conducted during the period from July 2007 to August 2008 on 180 children less than 5 years old with acute diarrheal episodes. They were randomly allocated into two groups; one of them received regular cow's milk formulas and the other received the same formula supplemented with Bifidobacterium lactis (107 CFU per gram of powder formula), for a duration of 4 weeks. Both groups were followed up for 3 months. Results: Probiotics - containing milk was able to decrease the mean number of diarrheal episodes: 1.15 (SD 1.10) in the intervention group versus 2.07 (SD 0.875) in the control group. It also reduced the mean frequency of stools per day in each attack (3.66 in the intervention group versus 4.93 in the control group) and the duration of subsequent episodes during the follow-up period. Conclusion: We can conclude from the study that administration of probiotics containing formulas during acute diarrheal episodes for 4 weeks could decrease the incidence of further diarrheal episodes, as well as, the severity of these episodes. The lower rates of child morbidity with probiotics treatment represent substantial benefits from a simple and inexpensive intervention that can be incorporated in existing efforts to control diarrheal disease.